Analysis of Warrant Issuing: on Abnormal Return - Mediaty; Abdul Hamid Habbe; Nurfaiqah Yunus (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the market reaction to abnormal stock returns before and after the issuance of warrants. This research data is secondary data. The population of this research are companies that issued warrants in the 2020-2023 period and are listed on the Indonesia Stock Exchange (BEI). The sampling technique for this research is a purposive sampling technique, namely selecting samples based on certain criteria. The sample for this research was 40 companies. The research uses an event study research model with an observation period of 10 days, namely 5 days before and 5 days after the announcement. The data analysis method used in this research uses the non-parametric statistical test Wilcoxon signed-rank test with the help of SPSS 29. The results of the research show that there is no influence on the issuance of warrants on abnormal stock returns.